2018
DOI: 10.1038/s41390-018-0062-4
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral blood flow and serum neuron-specific enolase in early-onset neonatal sepsis

Abstract: High CBF and cNSE could be useful markers for prediction of SAE. SAE impairs neurodevelopmental scales at 6 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 39 publications
(40 reference statements)
1
15
0
Order By: Relevance
“…The peak systolic velocity values in our study showed higher Mean values than that recorded by Sriparna et al 6 , which can be explained by the difference in timing of transcranial Doppler examination, and according to researches CBFV rise progressively with the postnatal age. 14 Also, our results were in accordance with those of Hashem et al 5 who found increased peak systolic velocity and lower resistance in neonates with EONS by examination of the ACA and MCA in preterm neonates at the third day after birth, and El Shimy et al 15 who found that neonates with EONS had raised cerebral blood flow and neuron-specific enolase in cord blood.…”
Section: Discussionsupporting
confidence: 91%
“…The peak systolic velocity values in our study showed higher Mean values than that recorded by Sriparna et al 6 , which can be explained by the difference in timing of transcranial Doppler examination, and according to researches CBFV rise progressively with the postnatal age. 14 Also, our results were in accordance with those of Hashem et al 5 who found increased peak systolic velocity and lower resistance in neonates with EONS by examination of the ACA and MCA in preterm neonates at the third day after birth, and El Shimy et al 15 who found that neonates with EONS had raised cerebral blood flow and neuron-specific enolase in cord blood.…”
Section: Discussionsupporting
confidence: 91%
“…Chorioamnionitis is a serious complication of pregnancy that is caused by bacterial infection or inflammation of the fetal amnion and chorionic membranes have been shown to be onset neonatal sepsis. Also velocities were higher in the case of sepsis-associated encephalopathy at newborns compared to group with neonatal sepsis and no encephalopathy (9).…”
Section: Introductionmentioning
confidence: 80%
“…The mean maternal age was 28±6.9 years. Median gravida was three (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). The mean gestational age at diagnosis of PPROM was 29±2.6 weeks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Post mortem histology in humans who died from septic shock at the early stage of sepsis, indicate that the neuropathological alterations may be the starting point for permanent neurological damage in survivors, leading to long-term SAE -associated symptoms (4,5,16,(27)(28)(29). Early-onset neonatal sepsis can lead to an extremely complex set of events, like brain injury, and survivors remain vulnerable to both short-and long-term neurodevelopmental morbidity, due to long-term changes in cerebral blood flow, the release of neuroinflammatory proteins and altered metabolism (30).…”
mentioning
confidence: 99%